2008
DOI: 10.1124/dmd.108.021543
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Hepatic Cytochrome P450 Isozymes in the Metabolism of Racemic 3,4-Methylenedioxy-Methamphetamine and Its Enantiomers

Abstract: ABSTRACT:The entactogen, 3,4-methylenedioxy-methamphetamine (MDMA), is a chiral drug that is mainly metabolized by N-demethylation and demethylenation. The involvement of cytochrome P450 (P450) isozymes in these metabolic steps has been studied by inhibition assays with human liver microsomes and, in part, with heterologously expressed human P450 isozymes. However, a comprehensive study on the involvement of all relevant human P450s has not been published yet. In addition, the chirality of this drug was not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 31 publications
6
64
0
Order By: Relevance
“…It has been suggested that CYP2D6 accounts for approximately 30% of MDMA metabolism, but involvement of other hepatic P450 enzymes, such as CYP1A2, CYP3A4, CYP2B6, and CYP2C19, has been reported (Meyer et al, 2008). However, the contribution of CYP3A4 and CYP1A2 to MDMA metabolism and what metabolites are being formed by these enzymes is less clear (Lin et al, 1992;Tucker et al, 1994;Kreth et al, 2000;Maurer et al, 2000).…”
mentioning
confidence: 88%
“…It has been suggested that CYP2D6 accounts for approximately 30% of MDMA metabolism, but involvement of other hepatic P450 enzymes, such as CYP1A2, CYP3A4, CYP2B6, and CYP2C19, has been reported (Meyer et al, 2008). However, the contribution of CYP3A4 and CYP1A2 to MDMA metabolism and what metabolites are being formed by these enzymes is less clear (Lin et al, 1992;Tucker et al, 1994;Kreth et al, 2000;Maurer et al, 2000).…”
mentioning
confidence: 88%
“…Most studies concerning polymorphism as a risk factor in acute MDMA intoxications refer to the polymorphism associated with the phase I enzyme CYP2D6, which has been reported in vivo (de la ) and in vitro (Tucker et al 1994;Ramamoorthy et al 2002). At present, it is thought to be the major enzyme yielding reactive MDMA catechol-metabolites (Tucker et al 1994;Lin et al 1997;Wu et al 1997;Delaforge et al 1999;Maurer et al 2000;Kreth et al 2000;de la Torre et al 2005;Segura et al 2005;Meyer et al 2008a). CYP2D6 is highly polymorphic, affecting its expression or activity and determining several metabolic groups as poor metabolizers (PMs, 1% Asians and $10% Caucasians), intermediate metabolizers (IMs $10-15% European population), extensive metabolizers (EMs), and ultra rapid metabolizers (UMs, frequent in Ethiopian and Saudi Arabian and $5% Caucasians), which are distributed over the entire population (Ingelman-Sundberg 2005).…”
Section: Polymorphism As Key For Mdma-mediated Toxicitymentioning
confidence: 99%
“…Phase I MDMA metabolism involves two main routes (Figure 1): (1) chain conversion by N-dealkylation to 3,4-methylendioxyamphetamine (MDA) mainly by CYP1A2, CYP2B6, and CYP2C19 or (2) O-demethylenation of the ring leading to 3,4-dihydroxymethamphetamine (HHMA) and 3,4-dihydroxyamphetamine (HHA) mediated by CYP2D6, CYP3A4, and CYP2C19. The cytochromes responsible of catalyzing the O-demethylation of the ring yield the catechol-metabolites (HHMA, HHA), which are more cytotoxic than the parent compound, indicating that MDMA bioactivation occurs after the opening of the ring (Kreth et al 2000;Jones et al 2005;Milhazes et al 2006;Meyer et al 2008b;Antolino-Lobo et al 2010). These metabolites can be oxidized to the corresponding ortho-metabolites, which generates reactive oxygen species (ROS) and reactive nitrogen species (RNS) (Monks and Lau 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CYP2D6 is the major route of metabolism, other P450 isozymes contribute to the overall metabolism of MDMA. 11,12,74,75 A recent study examined the potential drug-drug interactions between MDMA and caffeine. 76 Although, the authors report that there are no drug-drug interactions which significantly alter MDMA metabolism, the authors acknowledge the importance of the investigation into drug-drug interactions.…”
Section: Inhibition Studies With Rodent Isozyme: Cyp2d2mentioning
confidence: 99%